How does Market Access for Smallholders affect Export Supply? The Case of Tobacco Marketing in Malawi - Wouter Zant (Tinbergen Institute, 2016)
Transaction costs play a key role in the behaviour of smallholders in developing countries. We investigate smallholder tobacco cultivation in Malawi, Malawi's major export crop, and exploit the introduction of an additional tobacco auction floor to measure the impact of a reduction in transaction costs on smallholders' decisions on tobacco crop area and production. Estimations are based on annual data by Extension Planning Area, from the Ministry of Agriculture and Food Security, combined with data from other sources. A 10% reduction in transport cost is shown to lead to an increase in crop area and production of around 4% and 2.5%, respectively. Supply response runs along the extensive margin: both area and production increase, but production slightly less, leading to a decrease in yield, most likely because tobacco cultivation expands to less suitable areas and/or less productive farmers. In view of the non-experimental nature of the data, we confirm impacts by estimating a dose response function using generalised propensity scores. Supply response increases substantially within a distance to auction floor of less than 60km. We find no empirical support for conversion of crop area from maize and other crops into tobacco.
Keywords: D23; O13; O55; Q11; Q13; 330; transaction costs; market access; subsistence farming; food & cash crops; Malawi; Africa